2019
DOI: 10.1002/pip.3109
|View full text |Cite
|
Sign up to set email alerts
|

Tuning solar absorption spectra via carbon quantum dots/VAE composite layer and efficiency enhancement for crystalline Si solar module

Abstract: In this work, fluorescent carbon quantum dots (CQDs) composite transparent film with blue emission was prepared via hydrothermal fabrication, mixing with vinyl acetate-ethylene (VAE) emulsion, coated and cross-linked on the glass in sequence.This CQD/VAE film has good sticking ability and compatibility of sealing ethylenevinyl acetate (EVA) material and works well as luminescent downshifting (LDS) materials. Based on these features, we did a set of optical characteristics analysis for CQD/VAE film and inserted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Figure 4c shows EQE spectra of a device measured before and after application of a CQD@PMMA coating. The comparison of EQE spectra indicates that after deposition of the CQD@PMMA coating, the EQE response of the device in the blue region has improved [8][9][10]. The calculated J SC from EQE spectra obtained before and after deposition of the CQD@PMMA coating results in values of 16.31 mA cm −2 and 17.14 mA cm −2 , respectively, which exhibits the consistent improvement in J SC for the device after deposition of the CQD@PMMA coating.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Figure 4c shows EQE spectra of a device measured before and after application of a CQD@PMMA coating. The comparison of EQE spectra indicates that after deposition of the CQD@PMMA coating, the EQE response of the device in the blue region has improved [8][9][10]. The calculated J SC from EQE spectra obtained before and after deposition of the CQD@PMMA coating results in values of 16.31 mA cm −2 and 17.14 mA cm −2 , respectively, which exhibits the consistent improvement in J SC for the device after deposition of the CQD@PMMA coating.…”
Section: Resultsmentioning
confidence: 56%
“…Such a unique optical property of CQDs combined with their low-cost synthesis, non-toxicity, and chemical inertness make them very attractive for electronics, sensing, and bioimaging applications [5][6][7]. For example, carbon and graphene quantum dots were utilized recently for light management in silicon-based solar cells [8,9]. In both cases, the authors reported enhancement in the performance of silicon-based solar cells, owing to the carbon/graphene quantum dots coatings that emit additional down-converted photons in the visible spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…EVA has been proposed as a good candidate for the host material of the LDS layer. This resin is frequently used as an encapsulant in solar modules because of its high gas-barrier properties and negligible optical absorption loss. , The influence of the fabricated LDS films on the performance of a single c-Si solar module was investigated by changing the QD concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of fluorescent dye led to a 0.5-2% improvement in the short circuit current of the PV cell. Thereafter, the EQE enhancement of the PV module was reported by employing various LDS luminophores, namely organic dye-doped polymer layer, nanocrystal inorganic QDs, carbon dots, lanthanide metal doped oxide, metal oxide nanoparticles, and others, as shown in Figure 16c (Apostoluk et al, 2014;Bella et al, 2016;Dai et al, 2019;Gardelis & Nassiopoulou, 2014;Jalalah et al, 2018;Kalytchuk et al, 2014…”
Section: Application Of Luminophores To Pv Systemsmentioning
confidence: 99%